Efecto de la fertilización con mashi en el comportamiento agronómico del cultivo de arroz (Oryza sativa l.) en el cantón Rio Verde provincia de Esmeraldas - Quiñonez Pianchiche, Glady Francisca (2015)
This research was conducted in the enclosure The Laurel located 16 km from the Chumunde, Rio Verde Canton province of Esmeraldas parish. Its geographical location: 00 ° 19 '25 "south latitude and 80 ° 06' 12" west longitude, to a height of 30 m The objective was to determine the effect of restoring MASHI, at different doses, in variety INIAP 17 rice (Oryza sativa L.) in the province of Esmeraldas. The treatments were T1 (control), T2 (5100 gr Mashi), T3 (7200 gr Mashi) and T4 (10300 gr Mashi); completely randomized design agronomic variables were measured was used. This research is beginning to generate alternatives to an increasingly demanding market, taking a product that must be present in the daily diet; therefore, the addition of organic fertilizers such as Mashi. Mashi applications development and affect crop yield, above all in periods of maximum growth impacting positively plant physiology. T3 (7200 gr Mashi) and T4 treatments (10300 gr Mashi); showed statistical differences between treatments in the variables evaluated: Height of plant, number of tillers / plant, number of panicles per square meter, length of panicles, number of grains per panicle, percentage of fertile grains, thousand kernel weight, length grain and grain yield per square meter showed high statistical significance between treatments. Regarding the economic part treatment (control) had the highest benefit ratio with $ 3.81, meaning that for every $ 3 invested have a return of $ 0.81, followed by treatment T4 with $ 2.61, and treatment with less cost benefit ratio for Q3 was $ 2.55 As with fertilizer levels significantly influence the agronomic variables.